Gingival Disease - A Professional Approach for Treatment and Prevention 2019
DOI: 10.5772/intechopen.81815
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants and Periodontal Diseases

Abstract: Excessive reactive oxygen species production plays an important role in the pathogenesis of various chronic inflammatory diseases, including periodontal disease. Reactive oxygen species could damage the cells and the tissues. In the pathogenesis of periodontal diseases, the increased PMN count and activity cause a high rate of ROS release. This leads to increased oxidative stress in periodontal tissues. Periodontal tissues require adequate levels of antioxidants to prevent tissue damage caused by reactive oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…Several herbal extracts or natural compounds play an important role in treating various disease symptoms of periodontitis diseases due to their antioxidant properties [ 70 , 71 ]. Free radicals and reactive oxygen species play an essential role in an increased inflammatory response in the pathogenesis of periodontitis, which leads to the destruction of periodontal tissues and alveolar bone [ 8 , 72 ]. Antioxidant activity of S. baicalensis radix extract and binary mixtures were investigated by using two methods of different mechanisms, such as ABTS •+ radical cation assay and ferrous ion-chelating assay.…”
Section: Resultsmentioning
confidence: 99%
“…Several herbal extracts or natural compounds play an important role in treating various disease symptoms of periodontitis diseases due to their antioxidant properties [ 70 , 71 ]. Free radicals and reactive oxygen species play an essential role in an increased inflammatory response in the pathogenesis of periodontitis, which leads to the destruction of periodontal tissues and alveolar bone [ 8 , 72 ]. Antioxidant activity of S. baicalensis radix extract and binary mixtures were investigated by using two methods of different mechanisms, such as ABTS •+ radical cation assay and ferrous ion-chelating assay.…”
Section: Resultsmentioning
confidence: 99%
“…Chaplle et al [81,152,153], found lower total antioxidant concentration in the saliva of periodontitis patients when compared to health controls [24,154]. Salivary antioxidant levels (SOD, GPx, reduced GHS, ascorbic acid, alfa tocopherol, were observed to the lower in periodontal patients (Canacki) [146,[155][156][157]. In the present study, sulfhydryl (thiol), in gingival tissue, was observed in reduced quantities in the patients with gingivitis and periodontitis (groups B The pathological events which lead to the destruction of the periodontal tissues during gingival inflammation and periodontal destruction have been related to the effect of an imbalance between oxidants and antioxidants in patients with gingivitis and periodontitis (Sakalilioglu) [61,129,137].…”
Section: Discussionmentioning
confidence: 96%
“…Chaplle et al [81,152,153], found lower total antioxidant concentration in the saliva of periodontitis patients when compared to health controls [24,154]. Salivary antioxidant levels (SOD, GPx, reduced GHS, ascorbic acid, alfa tocopherol, were observed to the lower in periodontal patients (Canacki) [146,[155][156][157]. In the present study, sulfhydryl (thiol), in gingival tissue, was observed in reduced quantities in the patients with gingivitis and periodontitis (groups B and C), compared with the people from healthy group (Group A) [158,159].…”
Section: Discussionmentioning
confidence: 96%